Sexual Dimorphism from Foot Morphometry : A Study among Two Endogamous Groups of North India - Bhamini Sharma; Reena Singla; Vishal Verma (Institute of Medico-legal Publications Pvt Ltd, 2021)
Background: The present study aims to exhibit sexual dimorphism from foot morphometry and to find if it can be used as a tool for sex determination in forensic sciences among two endogamous groups (baniya, jats) of North Indian population. It is also aimed at providing anthropometric values for foot length and foot breadth and comparing them to existing data needed for the establishment of reference standard for the study groups on the basis of which various endogamous groups can be compared with one another and sexual differences established. Material and Methods: The present study was carried out at Department of Anatomy , MMIMSR Mullana –Ambala, on 400 subjects(100 males,100 females of each group) belonging to baniya and jats community of North India between 21-35 years of age. Foot morphometry was done with the help of osteometric board and results were statistically analysed. Results: The mean Foot length in males was 3 cm more than females with highly significant p value. The mean foot breadth of males was 1 cm higher than females with statistically significant p value. The mean foot length and foot breadth of jat group was more as compared to Baniya group with highly significant p value.The Mean Foot index ranges from 37(jats) – 36.9 (Baniya) males. In females,the range of mean foot index is between 37.73 (jats) -38.25 (baniya) . Conclusion: Males belonging to jat and baniya community had higher mean foot length,foot breadth than females. Among the study groups,jats males and females have longer and broader feet than baniya males and females.Foot index <37 is suggestive of male foot and >37 female foot and can be used as a reference point for sex determination among study groups.